DAMPAK PERSELINGKUHAN BAGI KELUARGA KATOLIK: ANCAMAN, PELUANG PASTORAL DAN STRATEGI - dagur, valdus; Mane Mori, Edmundus; Emil, Yohanis; Endi, Yohanes (STIPAS Keuskupan Agung Kupang, 2024)
This paper is intended to critically discuss the impact of infidelity on Catholic families, which includes threats, pastoral opportunities, and strategies needed in dealing with such cases. The method used in this paper is the case study method. This method allows the author to use some literature in the form of books, scientific journals, magazines, and online media that have relevance to the case raised in this paper. The case of infidelity raised in this study is part of the author's concern over events that have degraded and damaged the holiness of a marriage in the Catholic Church. In addition, infidelity has also become a very serious threat to the sustainability of Catholic families and of course has also threatened and damaged humans as moral creations of God. In this paper, the author attempts to critically analyze the case by paying attention to the guidelines of marital morality of the Catholic Church, especially based on the Code of Canon Law (KHK) and the apostolic call on family life. Based on the analysis, it was found that infidelity has damaged the lives of Catholic families and has had a significant impact on the decline of morality among families who have been bound in holy matrimony by the Catholic Church. In addition, infidelity has also destroyed the harmony that has been built in God's love. There are also pastoral strategies that we propose in this paper, including: the need for further formation for Catholic families regarding the consequences of holy marriage and monogamy. In addition, it is also necessary to hold meetings involving all Catholic families in order to create an atmosphere of intimacy among fellow families which ultimately brings awareness to care about the continuity of a holy and once-in-a-lifetime marriage.